There is more to action words than verbs: the case of action nouns - Abreu, Ana Maria (2021)
Response to: Marina Bedny, Alfonso Caramazza, Emily Grossman, Alvaro Pascual-Leone and Rebecca Saxe Journal of Neuroscience 29 October 2008, 28 (44) 11347-11353; DOI: https://doi.org/10.1523/JNEUROSCI.3039-08.2008